TEACHING SPEAKING BY ROLE-PLAY ACTIVITY - Fadilah Fadilah (IAIN MADURA, 2016)
The students often find some problems in practising English speaking. The problem frequently found is that their native language causes them difficult to use the foreign language. Other reason is because of motivation lack to practice the second language in daily conversation. They are also too shy and afraid to take part in the conversation. Many factors can cause the problem of the students’ speaking skills namely the students’ interest, the material, and the media among others including the technique in teaching English. There are many ways that can be done by the students to develop their ability in speaking English. The appropriate technique used by the English teacher also supports their interested in practising their speaking. One of the techniques that can be applied is role play.